Low-grade albuminuria in pulmonary arterial hypertension. (June 2019) - Nickel, Nils P.; de Jesus Perez, Vinicio A.; Zamanian, Roham T.; Fessel, Joshua P.; Cogan, Joy D.; Hamid, Rizwam; West, James D.; de Caestecker, Mark P.; Yang, Haichun; Austin, Eric D.
Low-grade albuminuria, determined by the urinary albumin to creatinine ratio, has been linked to systemic vascular dysfunction and is associated with cardiovascular mortality. Pulmonary arterial hypertension is related to mutations in the bone morphogenetic protein receptor type 2, pulmonary vascular dysfunction and is increasingly recognized as a systemic disease. In a total of 283 patients (two independent cohorts) diagnosed with pulmonary arterial hypertension, 18 unaffected BMPR2 mutation carriers and 68 healthy controls, spot urinary albumin to creatinine ratio and its relationship to demographic, functional, hemodynamic and outcome data were analyzed. Pulmonary arterial hypertension patients and unaffected BMPR2 mutation carriers had significantly elevated urinary albumin to creatinine ratios compared with healthy controls ( P  < 0.01; P  = 0.04). In pulmonary arterial hypertension patients, the urinary albumin to creatinine ratio was associated with older age, lower six-minute walking distance, elevated levels of C-reactive protein and hemoglobin A1c, but there was no correlation between the urinary albumin to creatinine ratio and hemodynamic variables. Pulmonary arterial hypertension patients with a urinary albumin to creatinine ratio above 10 µg/mg had significantly higher rates of poor outcome ( P  < 0.001). This study shows that low-grade albuminuria is prevalent in pulmonary arterial hypertension patients and is associated with poor outcome. This study shows that albuminuria in pulmonary arterial hypertension is associated with systemic inflammation and insulin resistance.